2021
DOI: 10.26555/jiteki.v7i2.21438
|View full text |Cite
|
Sign up to set email alerts
|

Design Prototype of Temperature and Humidity Control and Monitoring on Weaver Ant Cage based on Internet of Things

Abstract: Increasing market demand cannot meet the needs of the community, especially in the rainy season, because Kroto produced by weaver ants is of low quality and hard to find. Modern Kroto cultivation has many advantages compared to traditional searching in nature. The quality and quantity of Kroto lie in maintaining the temperature and humidity for weaver ants. The challenge is how to maintain the temperature and humidity inside the artificial nest of weaver ants. To help overcome the problems of modern weaver ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Additionally, with the widespread accessibility of smartphones and fast Internet, patients are increasingly using mobile applications to manage various medical requirements [15]. IoT is continuously evolving as a monitoring tool for a wide range of critical data through the utilization of sensors [17].…”
Section: Diabetes; Lora; Sensor; Wirelessmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, with the widespread accessibility of smartphones and fast Internet, patients are increasingly using mobile applications to manage various medical requirements [15]. IoT is continuously evolving as a monitoring tool for a wide range of critical data through the utilization of sensors [17].…”
Section: Diabetes; Lora; Sensor; Wirelessmentioning
confidence: 99%
“…The midfoot is the most common location for the highest plantar pressure [31]. A significant body of literature demonstrates an association between ulcer formation and increased foot pressure [17]. In a study conducted by Altayyar, it was revealed that foot pressure is also influenced by the patient's weight [32].…”
Section: Pressurementioning
confidence: 99%
“…IoT system continuously maintains connectivity to the internet network so that connected sensors or components can be monitored and controlled remotely (Panduardi et al, 2016) (Wardana et al, 2023). This technology is growing popular and attracts more research focus nowadays, such as in agriculture (Atmaja et al, 2021) (Prasetia et al, 2021) (Rahmatullah et al, 2023), animal cage control and monitoring (Farahiyah & Purnama, 2021), inventory systems (Wicaksono et al, 2021), vital human signs (Shahadi et al, 2021), monitoring system (Purnomo et al, 2021) (Wicaksono & Rahmatya, 2022), mobile security vehicles (Husni et al, 2021) and food (Riadi & Syaefudin, 2021).…”
Section: Introductionmentioning
confidence: 99%